The secret - Garwood, Julie (1992)
Proud, beautiful Judith Hampton journeys from her English home to meet the father she has never known. But even her escort, the powerful Laird Iain Maitland, cannot prepare Judith for the truth about her father--and the devastating secret that might change her life forever.
Includes preview of the author's Heartbreaker.
"... inspired Ransom"--Cover.
Series added by cataloger.
Keywords: Highlands (Scotland) -- Fiction; Scotland -- Social life and customs -- To 1603 -- Fiction; Fiction